Improving facilities maintenance management practices for government quarters apartment in Putrajaya / Mohd Azmi Saperi, Wan Zuriea Wan Ismail and Masreta Mohd - Saperi, Mohd Azmi; Wan Ismail, Wan Zuriea; Mohd, Masreta (UiTM Press, 2024)
Facilities Maintenance Management (FMM) practices such as preventive, corrective, and predictive maintenance are essential to ensure the effective operation of building systems. These practices involve regularly inspecting, fixing, and replacing building components to prevent failures and extend the building's lifespan. Maintaining highrise residential buildings is a multifaceted task that necessitates a comprehensive approach to ensure the optimal functioning of all building systems. To maintain their condition and functionality, government quarters apartments rely heavily on FMM practices. This study provides an in-depth examination of FMM practices in government quarters apartments in Putrajaya, Malaysia. While there is existing research on facilities and maintenance services, there needs to be a more specific focus on high-rise residential buildings, particularly those in government quarters. Therefore, the study aims to improve FMM practices in government quarters apartments in Putrajaya. The research objectives are to identify the current FMM practices in these high-rise residential buildings and develop strategies for improvement. The research methodology adopts a qualitative research approach by collecting data via semi-structured interviews with Putrajaya Corporation (PjC) strategic management level personnel and five (5) facility managers from FM service providers. The data has been analysed using ATLAS. Ti software is based on content analysis techniques. The findings reveal that FM practices for these case studies employed a comprehensive approach that includes technological advancement, sustainability, asset management, communication, outsourcing, performance metrics, and training. The recommendation for strategies permits future research improvements and contributes to the FMM body of knowledge in the context of high-rise buildings and government quarters apartments.